A comparative observational study on intrasphincteric injections with Botulinum toxin vs. enteral neuromodulation in chronic refractory constipation - Walther, Mona Anne; Müller, Hanna; Weiß, Christel; Carbon, Roman; Diez, Sonja; Besendörfer, Manuel (BMC pediatrics, 2023)
Purpose: Botulinum toxin injections in the anal sphincter apparatus (Botox) and enteral neuromodulation (ENM) are options for treatment of refractory chronic constipation. We present a retrospective comparative observational study. Patients and methods: From 2014 to 2022, pediatric patients with chronic constipation were either treated with Botox or ENM with continuation of conservative treatment. Comparison was conducted regarding the primary outcome variables defecation frequency, stool consistency, and abdominal pain. Secondary outcomes were fecal incontinence, enuresis, change of medication and safety of treatment. Results: 19 Botox patients (10 boys, 9 girls, 12 patients with Hirschsprung disease (HD), 7 patients with functional constipation (FC)) were compared to 24 ENM patients (18 boys, 6 girls, 12 HD patients, 7 FC patients). Groups differed significantly in age (5.0 years (Botulinum toxin) and 6.5 years (ENM), mean values, p-value 0.008). Improvement of constipation was seen in 68% (n = 13/19) of Botox and 88% (n = 21/24) of ENM patients (p = 0.153). Influence of etiology on therapeutic effects was not observed. Complications were minor. Conclusions: Botox and ENM can be considered as valuable and effective treatment options in refractory chronic constipation. Prospective, large-population studies should be designed to enable improved evidence.
Veröffentlicht: 08. September 2023
Gesehen am 24.11.2023